BEING CHRISTIANS IN THE ACEHNESE WAY: Illiberal Citizenship and Women’s Agency in the Islamic Public Sphere (JOURNAL OF INDONESIAN ISLAM, 2020)
This article examines the ways in which Acehnese Christian women’s identities expressed in the Islamic public sphere. The article argues that although theoretically Islamic Shari'a only applies to Muslims, its implementation in Aceh has a significant impact on the daily life of Christian women. The first part of the article presents a critical review regarding the Islamic sharia in Aceh dealing with the discourse of citizenship and the position of non-Muslim. Furthermore, drawing on agency theoretical frameworks, the authors describe the experiences of Christian women from diverse backgrounds to show how they became Christians in the Acehnese way. The article finally shows that Christian women's agencies as a minority in Aceh face a critical situation, although they remain independent and are not easily subdued by public sphere driven by the values and religious identities of the majority.